Eksplorasi Tata Pamer Museum Edukasi Universitas Negeri Malang - Rahmawati, Rahmawati; Sapto, Ari; Widiadi, Aditya Nugroho; Utami, Indah Wahyu Puji (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This research aims to explore comprehensive information about the display system of the State University of Malang (UM) Educational Museum collection which contains material from a collection of historical objects from the past, as well as identifying the role and potential for the sustainability of educational museums as a source of historical learning. The research method used is a qualitative approach with exploratory study analysis. Data collection through field observations, interviews, and documentation. The research results show that the UM Education Museum's display system has its characteristics and strategies for conveying effective information to visitors. In various challenges of the times, the existence of the UM educational museum can play an important role as a source of historical learning for students and the beautiful exhibition layout can have an impact on the sustainability of the UM educational museum in the future. The implications of this research provide input for the UM Education Museum and other museums in Indonesia in presenting museum exhibition arrangements that support learning and culture as a whole. Apart from that, the results of this research provide a real contribution to increasing insight into the exhibition layout of the Education Museum for visitors.